Conclusion - Daniel R. Mandelker (Washington University Global Studies Law Review, 2007)
This radical response to the compensation problem makes the Articles in this Symposium, which report on the international experience, most topical.
Keywords: Comparative law; Regulatory takings; Compensation (Law); Land use planning